Participation Of Beekeeping Group On Forest Sustainability In Muara Enim Regency, South Sumatra Province - Beni Rahmad; Nurhayati Damiri; Mulawarman Mulawarman (Sriwijaya Journal of Environment, 2021)
The dynamic nature of forest habitats is currently influenced by the impact of many disturbing factors, including fire, grazing, area fragmentation, land use conversion and invasion of communities outside forest areas. Fire and smoke from forest and land fires have a profound effect in producing landscape changes that also affect the regeneration of associated vegetation and animals. This study aims to determine the participation of the members of the beekeeper group in preserving the Subanjeriji production forest, in Muara Enim Regency, South Sumatra Province. The research was conducted using a survey method with a qualitative approach. This study also aims to determine the attitudes, knowledge and perceptions of beekeepers on the relationship between beekeeping and forest suistanibility. The results showed that beekeepers known the suistanibility of forest areas that affect the success of beekeeping (80%), so that 60% of beekeepers understand very well that forest and land fires can reduce bee populations and reduce the amount of honey bee. Most breekeepers also understand that the existence of forest plants is very beneficial to support honey production, so that the majority beekeepers are involved in land enrichment efforts with woody plants and most choose Multi Purpose Tree Species (MPTS) plants that produce fruit. Keywords: Participation, Beekeepers, Beekeeping, Sustainibility, HP Subanjeriji